2010
DOI: 10.1089/thy.2010.0189
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Laser Ablation of Cold Benign Thyroid Nodules: A 3-Year Follow-Up Study in 122 Patients

Abstract: After 3 years, the PLA technique achieved shrinkage of about 50% of the initial volume in a wide size range of benign cold thyroid nodules, with an improvement in local symptoms and signs. Side effects and failures were few although not negligible. PLA may be a new option for the management of benign cold thyroid nodules. Long-term controlled studies are required to establish the eligibility of patients for routine PLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
221
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 224 publications
(242 citation statements)
references
References 44 publications
16
221
2
3
Order By: Relevance
“…The rate of permanent hypothyroidism was low (only three patients) [63,65]. Valcavi et al have found that thyroid pericapsular bleeding developed in almost 2 % of patients, but this disappeared in 3-4 weeks.…”
Section: Complicationsmentioning
confidence: 94%
See 4 more Smart Citations
“…The rate of permanent hypothyroidism was low (only three patients) [63,65]. Valcavi et al have found that thyroid pericapsular bleeding developed in almost 2 % of patients, but this disappeared in 3-4 weeks.…”
Section: Complicationsmentioning
confidence: 94%
“…Corticosteroids were administered and the patients recovered completely after 6-10 weeks. Nerve compression because of perinodular edema is probably the cause of dysphonia [57,59,63]. Spiezia et al also reported transient dysphonia, lasting 24 h, which spontaneously resolved [73].…”
Section: Complicationsmentioning
confidence: 99%
See 3 more Smart Citations